Law Enforcement In The Implementation of Kuningan Regency Regional Regulation Number 6 of 2014 Against The Illegal Sale of Alcoholic Beverages - Gaza Muhammad Alghifari; Farah Aulia Lopiyana; Reka Maryam; Gunadi Rasta; Ari Nurhaqi Nurhaqi (Journal Research of Social Science, Economics, and Management, 2024)
The author focuses on the problems that occur related to the illegal sale of alcoholic beverages in Kuningan Regency, where in addition there is already a Regional Regulation that regulates the control and supervision of alcoholic beverages. The purpose of this study is to find out how the Implementation and obstacles to Regional Regulation Enforcement in the Illegal Sale of Alcoholic Beverages in Kuningan Regency. This research uses qualitative research methods and descriptive methods on enforcement theory according to Soerjono Soekanto. Data collection techniques are carried out using interview, observation, and documentation techniques. The findings obtained by the author in this study are that there are still many people who sell alcoholic beverages without a license. that in the Regional Regulation the control and supervision of alcoholic beverages is still not running optimally because there are still many inhibiting factors both from the community and Satpol PP as well as the main actors in the enforcement of the Regional Regulation. Therefore, to maximize the process of enforcing local regulations, Satpol PP is recommended to increase human resources, facilities and infrastructure, and budget. In addition, it is also necessary to hold socialization again to all people of Kuningan Regency.